Visual Semiotics Analysis Of Tokopedia X Bts Rm And Jhope Ads "Pay Bills And Buy Vouchers? Tokopedia Only" - Newahyu Jamalika Shintia (Jurnal Indonesia Sosial Teknologi, 2023)
Competition in the business world is getting tighter, especially in the e-commerce industry, where consumers have many varied product choices. The emergence of innovative products in a short time encourages the company to develop its products so as not to lose to competitors. Consumers have great power in making choices, and brands influence consumer decisions. This research uses a qualitative approach with case studies as a research method. Data is collected through qualitative documents and audio-visual materials, especially advertisements. Advertising conveys information about the product and seeks to influence and persuade consumers to choose the product. Through Tokopedia x BTS RM &; JHope ad analysis: "Pay Bills and Buy Vouchers? Tokopedia Saja" in early 2020, this research revealed how modern advertising not only offers products but also creates a lifestyle and meets consumer needs easily and practically. This advertisement reflects Tokopedia's efforts in reaching the target market by focusing on visual elements and messages relevant to various groups of people, including those with special needs.